1990
DOI: 10.1111/j.1476-5381.1990.tb14650.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in hepatic drug accumulation and enzyme induction after chronic amiodarone feeding of two rat strains: role of the hydroxylator phenotype?

Abstract: It has previously been shown that the extent of hepatic phospholipidosis induced by chronic amiodarone treatment correlates with the degree of drug accumulation in liver tissue. To investigate a possible influence of pharmacogenetic factors, biochemical and morphological investigations were carried out in two rat strains differing in debrisoquine hydroxylation. Plasma and liver tissue concentrations of amiodarone and its main metabolite, desethyl‐amiodarone, were significantly higher in rats with deficient hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Strain-related differences in the biotransformation to desethylamiodarone may account for the observe d differences in response to amiodarone. In a recent study, Pirovino et al (1990) clearly demonstrated that the amiodarone-induced pulmonary phospholipidosis was associated w ith a significant increase in the activities of hepatic microsomal cytochrome P-450 and NADPH cytochrome c reductase, and with an elevation in serum desethylamiodarone in DA strain rats. In contrast, a lack of effect on morphology and phospholipid content was accompanied by no marked change in the microsomal mixed-function oxidase system in am iodarone-treated Sprague-D aw ley rats.…”
Section: Lungmentioning
confidence: 97%
“…Strain-related differences in the biotransformation to desethylamiodarone may account for the observe d differences in response to amiodarone. In a recent study, Pirovino et al (1990) clearly demonstrated that the amiodarone-induced pulmonary phospholipidosis was associated w ith a significant increase in the activities of hepatic microsomal cytochrome P-450 and NADPH cytochrome c reductase, and with an elevation in serum desethylamiodarone in DA strain rats. In contrast, a lack of effect on morphology and phospholipid content was accompanied by no marked change in the microsomal mixed-function oxidase system in am iodarone-treated Sprague-D aw ley rats.…”
Section: Lungmentioning
confidence: 97%
“…Rats are the most common laboratory model for investigating vitamin A metabolism. However, inter-strain differences in both vitamin A metabolism and responsiveness to drug administration are known to exist among rats, making extrapolation of data from one strain to another difficult (Pirovino et al 1990;Seifert et al 1991;Lahmame & Armario, 1996;Tuitoek et al 1996;Schindler et al 2002). Therefore, another factor considered when designing the present study was the rat strain.…”
mentioning
confidence: 99%